2016
DOI: 10.1158/1940-6207.capr-15-0439
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol Enhances the Chemopreventive Efficacy of 5-Fluorouracil on an Intermediate-Term Model of Azoxymethane-Induced Colorectal Tumors in Rats

Abstract: Colorectal cancer is a common cancer with high mortality rate. Despite being the standard anti-colorectal cancer drug, 5-fluorouracil (5-FU) exhibits only limited therapeutic benefits. Herein, we investigated whether paricalcitol, a synthetic vitamin D analogue with potential antitumor properties, would enhance the chemopreventive efficacy of 5-FU on an intermediate-term (15 weeks) model of colorectal tumors induced by azoxymethane (AOM) in rats. After AOM injection, 5-FU was administered during the 9th and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Preclinical studies in animal models have demonstrated that vitamin D treatment may inhibit colorectal [119][120][121][122][123][124], prostate [15,[125][126][127][128][129] and breast cancer [126,[130][131][132] development, by reinforcing the concept that vitamin D plays a crucial role in carcinogenesis.…”
Section: Animal Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Preclinical studies in animal models have demonstrated that vitamin D treatment may inhibit colorectal [119][120][121][122][123][124], prostate [15,[125][126][127][128][129] and breast cancer [126,[130][131][132] development, by reinforcing the concept that vitamin D plays a crucial role in carcinogenesis.…”
Section: Animal Studiesmentioning
confidence: 88%
“…Vitamin D may also act in combination with different therapies, by inducing an antiproliferative additive effect. Indeed, in both mouse and rat chemically induced colorectal cancer models (AOM-induced, 1,2-dimethylhydrazine dihydrochloride (DMH)-induced and DMH-dextran sodium sulfate (DSS)-induced) and xenografts models, vitamin D analogs, such as paricalcitol and PRI-2191, in combination with 5-fluorouracile (5-FU) or metformin, diminished the risk to develop early colon neoplasia by controlling the early stage of carcinogenesis and reducing or delaying cancer growth through a specific cell cycle arrest and apoptosis induction, when compared to the 5-FU and metformin treatment alone [122][123][124]. The reported effects were triggered by several synergistic molecular mechanisms such as antiproliferative and antiinflammatory processes.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in some published articles, the accession number of the reference sequence used is not indicated or the qPCR is not well designed or described (i.e., the primer sequence is missing or contains mistakes, primers are not specific). On the basis of the aforementioned data, in this study we provide a well-designed and described qPCR protocol according to the MIQE (Minimum Information for Publication of Quantitative Real-Time PCR Experiments) guidelines (Bustin et al., 2009) for 17 genes routinely studied in DMH/AOM CRC rat model (El-Shemi et al., 2016; Kensara et al., 2016; Islam et al., 2016; Qie & Diehl, 2016; Rivera-Rivera & Saavedra, 2016; Rubio, 2017; Al-Henhena et al., 2015; Tan et al., 2015; Gamallat et al., 2016; Walter et al., 2010). Moreover, we also analyse two reference genes commonly used in this carcinogenesis model.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that several groups have investigated the combination of 1,25(OH) 2 D 3 with 5-FU in different colorectal cancer models. Using an azoxymethane-induced colorectal cancer rat model, El-Shemi et al [ 20 ] and Refaat et al [ 21 ] demonstrated that the combination of paricalcitol (a synthetic VDR analog), in case of the former, and vitamin D 3 , in case of the latter, together with 5-FU, led to significant reductions in the number of tumors grown. Additionally, both studies illustrated enhanced interference of this combination with the Wnt signaling pathway, through decreasing the expression of Wnt and β-catenin, and the induction of the pathway’s inhibitor, Dkk1.…”
Section: Introductionmentioning
confidence: 99%